História local e ensino de história: um estudo dos modos de pensar o espaço da cidade de Fortaleza e sua relação com a Ditadura 1964-85 - Cruz, Sandoval Matoso da (2023)
The present work seeks to make a reflection about the teaching of History and the military dictatorship in Brazil. This topic is quite delicate for professors, based on the understanding and also on the use of Local History and Public History as powerful resources to face the issue. Therefore, firstly it was made a spatial (city of Fortaleza), temporal (1960-1980) and thematic (Military Dictatorship) cut in order to exercise the analysis of historicity and the different layers of time dealt when transiting in a city. Afterwards, there was a brainstorming session with students from different schools (public and private) at the Mentimeter platform. The goal was to capture their initial impressions on themes related to the dictatorship, followed by the application of a quiz to detail understandings. From this point, a spatial script was elaborated, materialized in a sensory, interactive and illustrated map; and an action plan was created to enable the classroom to experience the use of the city as a textbook. The project is called “Nos porões da ditadura” which means “In the basements of the dictatorship”. Finally, it was noticed that teachers,who want to relate Public History and Local History with the taught History, need to deal with concepts that help students to understand more critically the historical and social reality that surrounds them. As a result, 11 concepts were listed and considered essential when thinking about History teaching within the relationship with Public History and City History. Their definitions were briefly detailed based on reference authors, in a compact inventory, which is a mandatory instrument for the proposal lesson application and also the better handling over the interactive map